2021
DOI: 10.1159/000515893
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Insulin, Metformin, and Glyburide on Perinatal Complications of Gestational Diabetes Mellitus: A Systematic Review and Meta-Analysis

Abstract: <b><i>Aim:</i></b> This systematic and meta-analysis was conducted to evaluate the efficacy and safety of insulin, metformin, and glyburide on perinatal complications for gestational diabetes mellitus (GDM). <b><i>Methods:</i></b> Medline (PubMed), EMBASE, The Cochrane Library (Cochrane Database of Systematic Reviews, Cochrane Central Register of Controlled Trials [CENTRAL], and Cochrane Methodology Register), Web of Science (Science and Social Science Citation I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…However, opinions regarding the effect of metformin for GDM on maternal and infant outcomes vary. In our study, both DMA and NMA demonstrated that metformin reduced the incidences of neonatal hypoglycemia and NICU admission compared to insulin, and SUCRA sequencing found that the incidence of neonatal hypoglycemia was lowest in the metformin group, consistent with a previous meta-analysis by Wang et al [68][69][70][71][72]. Since glucose can pass through the placenta, high maternal blood glucose leads to increased fetal glucose levels, resulting in excessive insulin secretion in the fetus.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, opinions regarding the effect of metformin for GDM on maternal and infant outcomes vary. In our study, both DMA and NMA demonstrated that metformin reduced the incidences of neonatal hypoglycemia and NICU admission compared to insulin, and SUCRA sequencing found that the incidence of neonatal hypoglycemia was lowest in the metformin group, consistent with a previous meta-analysis by Wang et al [68][69][70][71][72]. Since glucose can pass through the placenta, high maternal blood glucose leads to increased fetal glucose levels, resulting in excessive insulin secretion in the fetus.…”
Section: Discussionsupporting
confidence: 90%
“…However, Tarry et al [80] suggested that metformin increases the risk of macrosomia in offspring, whereas the study by Wang et al produced conflicting results. Their results suggest that metformin can reduce the incidences of macrosomia, cesarean section, and gestational hypertension compared with insulin treatment in pregnant women with GDM [68,69]. The main reason behind the differences between the results of the analyses may be that the inclusion and exclusion criteria applied were inconsistent across studies, leading to certain differences between the data in the included literature and, in turn, to differing research results.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed a lower risk for preeclampsia, macrosomia, neonatal hypoglycemia, and hypertensive disorders as well as better outcomes in maternal weight gain and glycemic control. No difference was observed in rates of caesarean section, neonatal respiratory distress and preterm birth compared to insulin treatment alone [ 13 , 14 , 15 , 16 , 17 ]. There is insufficient evidence on the long-term effects of prenatal exposure to metformin (especially because it crosses the placenta).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the aforementioned study, insulin was the only antidiabetic medication used in our cohort. In contrast to insulin [ 22 ], other antidiabetic medications such as metformin or glyburide are known to cross the placenta and have been associated with adverse neonatal outcomes such as preterm birth and neonatal hypoglycemia, respectively [ 23 - 25 ]. Thus, the effect of antidiabetic medication on neurodevelopment, indirectly as a consequence of adverse neonatal outcomes or through direct interference with fetal brain development, could not be ruled out in the previous studies.…”
Section: Discussionmentioning
confidence: 99%